KONTAMINASI AL QUR’AN DENGAN BAHASA-BAHASA KABILAH ARAB DAN NON ARAB (‘AJAM) MENJADI METODE PEREKAT UMAT - Mustofa, Ahmad (Mahad Aly Al Fithrah Press, 2019)
Before Islam came the Arab nation was a nation branch out that has a diversity of languages, civilization and culture. In the time of their glory they were known with their hard, fanatical character and pleasure in poems (Poetry) that have literary values High language. The poems are made as their expertise and honor in pride proud of his own tribe by holding it the beauty poetry contest on the market known as Suqu ‘Ukaz where each of the most beautiful poems will be posted on the wall ka'bah besides that the world criticizes each other Language is not a thing the taboo at that time but is a necessity that has been entrenched. Language and literary criticsvery fond of criticizing every occurrence of language and poetry just as An Nabighah Al Dzibani got it the nickname of Hamra 'Qubbah (Red Dome) in judgment a literary work1. The world criticizes it as it continues continued until Al Quran was revealed to the prophet Muhammad SAW so it cannot be denied if the Qur'an also received scathing criticism from infidels Makkah. With so many tribes there is dialegpun diverse where each tribe has a language difference and dialeg, this diversity of languages ??continues to stick from time to time the time until Islam came. Some of the prophet's friends read Al The Quran with the dialeg of their own tribe is this is the reason for the emergence of differences in reading in Al The Quran but despite this every narrated passage from friends is true the law is due to them reciting the reading before the prophet directly. Indications that say that the Qur'an is contaminated with the languages ??of the Arabic (local) tribe and the Non Arabic Language (‘Ajam) is a prophetic hadith which reads